Design and Analysis of Phased Array Antenna Beam Steering For Satellite Tracking - Ng, Chee Kyun (2002)
Nowadays achievements on mobile satellite system (MSS) communication give a great concern for research in global wireless communication fields. This has prompted the development of several Non Geostationary Earth Orbit (Non-GEO) satellite systems that promises worldwide connectivity for real-time communications. The mobility of Non-GEO satellite systems require a high directivity satellite tracking technique and a reliable inter satellite handover algorithm to ensure that connectivity between two end users are not interrupted as a result of satellite movement. In this thesis, phased array antenna has been proposed to obtain high directivity beam for satellite tracking. In order to do this, the phased array antenna mathematical model has been developed. This mathematical model has demonstrated that a narrow beam with high directivity could be generated. By changing the phase of the exciting currents in each element of antenna array, the radiation pattern could be varied through space. Thus, the generation of multiple and steerable beams also could be depicted by varying the phase shift of phase shifter with appropriate spacing between each elements to be sufficiently large. It is also shown here that the generated radiation beamwidth can be controlled by varying the number of antenna elements. It was found that the beamwidth reduces exponentially with the increment of the number of antenna elements.